Combined therapy of arterial hypertension, chronic heart failure and depressive disorders bу АСЕ inhibitor and diuretics - T. A. Dronova; D. V. Polyakov (Кардиоваскулярная терапия и профилактика, 2008)
Aim. To study antihypertensive effects of combined therapy with an ACE inhibitor and various diuretics, to assess its influence on quality of life (QoE) and chronic heart failure (CHF) symptoms and signs among patients with Stage II-III arterial hypertension (AH) of very high risk.Materials and methods. In total, 86 hospitalized patients with AH and CHF were administered enalapril combined with either hydrochlorothiazide (HCT) or indapamide (Ind). Dynamics of blood pressure (BP) level, CHF severity (by clinical condition evaluation scale, CCES), and cardiovascular risk level (by SCORE, Systemic Coronary Risk Evaluation, scale) were assessed. Before the therapy start and at discharge, patients were administered Center for Epidemiologic Studies-Depression scale (CES-D). Self-evaluated health was measured by Visual Analog Scale (VAS).Results. Combined therapy was associated with substantial decrease in systolic, diastolic, pulse and mean BP levels in both groups. More pronounced reduction of mean BP indices (p<0,002), accompanied by CHF clinics improvement (p<0,001) and positive QoE dynamics (p<0,0001), was observed in the group of enalapril and HCT In both groups, the levels of fatal cardiovascular event risk reduced from high (5-10 %) to low (<5 %). Psychological status improvement was demonstrated by greater CES-D score reduction in subjects receiving enalapril and HCT (p<0,02).Conclusion. Combination of enalapril and HCT was more effective than that of enalapril and Ind, in terms of its effects on mean BP levels, subjective QoE, and CHF clinics in AH patients.